The influence of objective and subjective knowledge on attitude and willingness to pay veterinary control number-certified livestock food product - Syahlani, Suci Paramitasari; Wankar, Tian Jihadhan; Triatmojo, Agung (Universitas Sebelas Maret, 2023)
Objective: This study aims to analyse the effect of objective and subjective knowledge on attitude and willingness to pay for veterinary control number certified-livestock food products.Methods: The study was conducted by survey design. Respondents were determined by a judgmental sampling method with the criteria that respondents were at least 19 years old and contribute as full or part decision makers of food buying for him/herself or their families. Data were collected online by using questionnaires and analyzed using structural equation modelling with partial least squares software.Results: The results showed that objective knowledge (β=0.20, t=1.97) positively affected attitude toward VCN-certified livestock food product, while subjective knowledge did not affect (β= -0.10; t=1.44). Then, attitude toward VCN-certified livestock food product (β=0.29; t=3.73) affected willingness to pay for VCN-certified livestock food product. Furthermore, willingness to pay was influenced directly by subjective knowledge (β=0.34; t=6.37) but objective knowledge was not influenced significantly (β=-0.07; t=1.26). The R2 value for attitude toward VCN-certified livestock food product was 0.05 and willingness to pay was 0.18.Conclusions: This study concluded that willingness to pay for VCN-certified livestock food product is directly influenced by subjective knowledge, and indirectly by objective knowledge through attitude toward VCN-certified livestock food product.